Metaproteomics reveals age-specific alterations of gut microbiome in hamsters with SARS-CoV-2 infection - Marybeth Creskey; Fabiola Silva Angulo; Qing Wu; Levi Tamming; Emily E. F. Fekete; Kai Cheng; Zhibin Ning; Angela Wang; Patrícia Brito Rodrigues; Vinícius de Rezende Rodovalho; Marco Aurélio Ramirez Vinolo; Daniel Figeys; et al. (Gut Microbes)
The gut microbiome’s pivotal role in health and disease is well established. SARS-CoV-2 infection often causes gastrointestinal symptoms and is associated with changes of the microbiome in both human and animal studies. While hamsters serve as important animal models for coronavirus research, there exists a notable void in the functional characterization of their microbiomes with metaproteomics. In this study, we present a workflow for analyzing the hamster gut microbiome, including a metagenomics-derived hamster gut microbial protein database and a data-independent acquisition metaproteomics method. Using this workflow, we identified 32,419 protein groups from the fecal microbiomes of young and old hamsters infected with SARS-CoV-2. We showed age-specific changes in the expressions of microbiome functions and host proteins associated with microbiomes, providing further functional insight into the interactions between the microbiome and host in SARS-CoV-2 infection. Altogether, this study established and demonstrated the capability of metaproteomics for the study of hamster microbiomes.